2014
DOI: 10.1136/bmjopen-2014-006020
|View full text |Cite
|
Sign up to set email alerts
|

One lithium level >1.0 mmol/L causes an acute decline in eGFR: findings from a retrospective analysis of a monitoring database

Abstract: ObjectivesLithium is a mainstay of bipolar disorder treatment, however, there are still differences in opinion on the effects of lithium use on renal function. The aim of this analysis was to determine if there is an association between short-term exposure to various elevated lithium levels and estimated-glomerular filtration rate (eGFR) at ≤3 months, 6 months (±3 months) and 1 year (±3 months) follow-up.SettingNorfolk-wide (UK) lithium register and database.Participants699 patients from the Norfolk database.P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 14 publications
1
28
0
Order By: Relevance
“…In addition, there may be benefits in monitoring serum concentrations of lithium levels relatively frequently, especially in elderly patients. It has been suggested that lithium levels should be monitored every 3 months since even a single occurrence of a level higher than 1.0 mEq/L may result in a modest but significant decrease of the GFR lasting for at least 3 months (Bauer et al 2006 ; Van Beneden et al 2011 ; Kirkham et al 2014 ; Davis et al 2015 ; Shine et al 2015 ). In general, we would emphasize the importance of appropriate selection of patients for long-term lithium treatment, maintaining them on minimum effective doses and daily trough serum concentrations especially for older populations, and regular monitoring to assess adherence to prescribed treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there may be benefits in monitoring serum concentrations of lithium levels relatively frequently, especially in elderly patients. It has been suggested that lithium levels should be monitored every 3 months since even a single occurrence of a level higher than 1.0 mEq/L may result in a modest but significant decrease of the GFR lasting for at least 3 months (Bauer et al 2006 ; Van Beneden et al 2011 ; Kirkham et al 2014 ; Davis et al 2015 ; Shine et al 2015 ). In general, we would emphasize the importance of appropriate selection of patients for long-term lithium treatment, maintaining them on minimum effective doses and daily trough serum concentrations especially for older populations, and regular monitoring to assess adherence to prescribed treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Adverse effects with regard to renal and thyroid function frequently occur . A significant decline in renal function has been reported in patients treated with lithium, in rare cases resulting in renal failure . Thyroid function may decline, with a risk of developing goiter.…”
Section: Introductionmentioning
confidence: 99%
“…15 In this clinical vignette, the recent initiation of hydrochlorothiazide likely led to a cascade of events: increased lithium level, acute nephrogenic diabetes insipidus, dehydration, AKI and reduced renal clearance, leading to further lithium level increases. 6 In this case, permanent renal 4 and neurologic damage are unlikely. 2 The patient also had a history of poor psychiatric course following lithium discontinuation.…”
mentioning
confidence: 99%
“…5 Consequently, lithium and renal function need monitoring every 3 months with aging. 4,5 Nephrogenic diabetes insipidus also increases toxicity risk, possibly through a feedback loop of elevated lithium levels causing acute diabetes insipidus and leading to further diuresis and lithium level elevations. 6 Other risk factors include medications commonly prescribed in late life, such as diuretics, loop diuretics, angiotensin converting enzyme inhibitors, angiotensin II receptor blockers and nonsteroid anti-inflammatory drugs, which can increase lithium levels up to 50%.…”
mentioning
confidence: 99%
See 1 more Smart Citation